2016
DOI: 10.1038/srep23317
|View full text |Cite
|
Sign up to set email alerts
|

SIK2 regulates fasting-induced PPARα activity and ketogenesis through p300

Abstract: Fatty acid oxidation and subsequent ketogenesis is one of the major mechanisms to maintain hepatic lipid homeostasis under fasting conditions. Fasting hormone glucagon has been shown to stimulate ketone body production through activation of PPARα; however, the signal pathway linking glucagon to PPARα is largely undiscovered. Here we report that a SIK2-p300-PPARα cascade mediates glucagon’s effect on ketogenesis. p300 interacts with PPARα through a conserved LXXLL motif and enhances its transcriptional activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For examples, fasting stimulated the SIK2‐p300‐PPARα pathway to mediate glucagon signalling and regulated lipid metabolism (Zhang et al . ). Fasting also induced autophagy by activating AMPK and then directly activated phosphorylation of Forkhead box O3 (FoxO3) and the Unc‐51‐like kinase 1 (Ulk1) without repression of mTOR (Mammucari et al .…”
Section: Discussionmentioning
confidence: 97%
“…For examples, fasting stimulated the SIK2‐p300‐PPARα pathway to mediate glucagon signalling and regulated lipid metabolism (Zhang et al . ). Fasting also induced autophagy by activating AMPK and then directly activated phosphorylation of Forkhead box O3 (FoxO3) and the Unc‐51‐like kinase 1 (Ulk1) without repression of mTOR (Mammucari et al .…”
Section: Discussionmentioning
confidence: 97%
“…Von Meyenn and coworkers have shown that glucagon stimulation induced Lys259 acetylation of Foxa2, which plays an important role in glucagon-stimulated fatty acid oxidation (von Meyenn et al 2013). Our previous work also pointed out that glucagon could promote fatty acid oxidation through releasing the inhibitory effect of SIK2 on p300, which binds to PPARα and promotes PPARα activity (Zhang et al 2016). Thus, glucagon regulates fatty acid oxidation genes expression and PPARα activity through multiple mechanisms.…”
Section: :2mentioning
confidence: 90%
“…In addition, transcription factor PPARα was likely activated in the liver of A. davidianus after prolonged fasting by Upstream Regulator Analysis in IPA. The activated PPARα by fasting promoted the expression of fatty acid oxidation and ketogenesis-related genes in synergy with other fastingrelated transcription factors, such as CREB3L3 (Nakagawa et al, 2016), p300 (Zhang et al, 2016), and PGC-1α (Rodgers and Puigserver, 2007). These results indicate that the enhanced fatty acid oxidation is needed to provide energy for the A. davidianus after prolonged fasting and can also explain why A. davidianus can survive for long periods of food deprivation.…”
Section: Fatty Acid β-Oxidation and Ketogenesis Are Up-regulated Durimentioning
confidence: 79%